Institutional Provision of ICT Infrastructure and Services- A Linchpin for Learner Participation in Distance Learning Programmes; The Case of Distance Learning Students Undertaking Diploma Course in Selected Distance Training Centers of the College of Edu - Evariste, Gahima; Omondi, Bowa; Nzuki , Peter (African Journal of Education and Practice, 2022)
Purpose: The purpose of the study was to investigate provision of ICT infrastructure and services on learner participation in distance learning programmes in the College of Education, University of Rwanda which were evaluated in light of five research questions that aimed to establish the extent to which provision of Video conferencing facilities, digital video and CD-ROMs influence learner participation in distance learning; assess the extent to which provision of internet connection points influence learner participation in distance learning; establish the extent to which the availability of electronic mail accounts and availability of computers for teaching and learning influence learner participation in distance learning; and to assess the extent to which access to electronic library influence learner participation in distance learning programmes. Methodology: The study used both qualitative and quantitative approaches to collect data and embraced by a cross- sectional survey study. A sample study comprised of 315 students out of 1,474 that formed the target population. Findings: The findings showed that ICT infrastructure and services positively and significantly influenced learner participation in distance learning in the College of Education with, Î²=374.272, t= 7.261, p=0.000<0.05. Thus, the null hypothesis Hâ‚’ was rejected and the alternative Hâ‚ accepted that provision of ICT infrastructure and services has a significant influence on learner participation in distance learning. Overall, the results from analysis of data showed that distance learners disagreed that ICT infrastructure and services were adequately provided with (M= 1.68, St. = 0.43). This meant that ICT infrastructure and services are not adequately provided to learners in the programme. This may hinder full participation of learners in the programme since learners usually depend on ICT infrastructures for their studies. The coefficient of determination for the influence in the provision of ICT infrastructure and services on learner participation was R2=0.058. This meant that 5.8% of the variance in learner participation was explained by provision of ICT infrastructure and services. Unique Contribution to Theory Practice and Policy: The theory in this study was validated and drew conclusion that measurable forms of ICT infrastructure and services such as internet connectivity, audio and video conferences, e-library services and other facilities were not statistically significant. Therefore, the unique contribution to this study calls for the policy makers to lay down funding mechanisms to support functionality of the university of Rwanda in order to be able to provide the necessary support services to learners and harness digital technologies in education delivery. In practice, the university of Rwanda in its strategic directions should ensure that it introduces degree programmes not only for in-service teachers but also in other disciplines in order to attract more people to participate in the distance learning programmes. The study will also open up new room for academic discussions in the pedagogic perspectives on what works well for learners in terms of interactions, discussions and communication between instructors and themselves.